Reforming the Maldivian penal code with reference to punishment of imprisonment - Shafy, Mohamed Affan (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2020)
The purpose of this thesis is to identify issues related to the use of imprisonment as a general form of punishment in the Penal Code of Maldives and to propose areas of reforms to the punishment of imprisonment to Maldives. In this study two main areas for reform were identified; firstly, since Maldives is a 100% Islamic country, the philosophies, aims, purposes of punishment and punishment of imprisonment were identified from Islamic Shari'ah. Since confirmation to the tenets of Islam is a requirement for all laws in Maldives by its constitution a Shari'ah punishment benchmark was derived under Article 10 of the Constitution of Maldives 2008. It was established that Shari'ah punishments were of 3 main types in Islamic criminal law, these are hudud (fixed), qisas (retaliatory) and ta'zir (discretionary) punishments. To suggest Shari'ah reforms to the Maldivian Penal Code, Islamic penal systems from Brunei Darussalam and Malaysia were analyzed. Secondly, for the reduction of meting imprisonment as a general form of punishment, different types of alternative punishment forms and application of penal laws were identified from the Nordic region where the penal systems in the Nordic region seldom used imprisonment unless for major crimes; and even in the instances of imprisonment, the punishment is focused on reforming the offender. The Nordic penal punishment model was found to be more compliant with the punishment philosophy of Shari'ah. This research identified that Maldivian Penal Code 9/2014 had imprisonment as a primary punishment form for all types of offences and an unrestricted discretion on punishment was given to judges. It was also found in this study that Maldivian prisons were not suitable to keep prisoners as they are not operated in accordance with laws of Maldives, Shari'ah punishment objectives and international human rights conventions and treaties. To identify areas of punishment reform all the 160 offenses mentioned in the Penal Code of Maldives 9/2014 were analyzed under the Shari'ah benchmark, it was found that offences that are applicable under hudud or qisas categories were allocated imprisonment sentences. In order for the penal laws of Maldives to comply with the Shari'ah benchmark whilst reducing imprisonment as a general form of punishment and introducing alternative punishment forms, it was recognised in this research that Maldives would have to follow a mixed model of a codified Islamisation model in terms of hudud and qisas punishments and a harmonization reformation model in terms of reforms on alternative forms of punishments under ta'zir. The findings of this study will help stakeholders in reforming Maldivian Penal Code with reference to the punishment of imprisonment to be compliant with the Shari'ah, Constitution of Maldives and international best practice.